Illocutionary Speech Acts on Digital Tourism Posters to Develop Tourism in Bangkalan, Madura - Siti Nurhaliza Adinda Arigama; Tri Pujiati; Meria Zakiyah Alfisuma (Journal of Social, Culture, and Language, 2023)
Digital tourist posters are a breakthrough in tourism development efforts in the Bangkalan region, Madura. As one of the areas on Madura Island, Bangkalan has a very good and potential tourist area. However, unfortunately, this potential is still not optimal for the wider public to know because there is still a lack of promotion of this tourist area. This research attempts to look at the directive illocutionary utterances contained in digital tourist posters as an effort to develop tourism in Bangkalan, Madura. Digital tourist posters are packaged using a variety of invitational language so it is necessary to study the use of directive illocutions to see the pragmatic power of the poster. This research with a qualitative descriptive design uses data collection techniques in the form of observation and documentation techniques. In this research, the author only focuses on the type of directive illocutionary speech act which focuses on the invitation speech used in digital tourist posters. This research uses Searle's theory of directive illocutionary speech acts. In the results of research related to directive illocutionary speech acts on digital tourist posters, the author found several utterances that show the use of illocutionary acts in digital tourist posters. Some uses of verbs that show directive illocutionary are directive verbs (come on, don't forget, and let's). In the digital tourist poster, there are 3 languages used, namely Madurese, English, and Madurese so variations in the use of directive speech are found in the digital tourist poster. Overall, it can be said that the use of directive illocutions in these three languages has been able to provide effective illocutionary power to attract tourists to visit Bangkalan, Madura. Keywords: Digital Tourism Poster, Directive, and Bangkalan Illocutionary Speech Acts